Genome-Wide Identification and Functional Analysis of Polyamine Oxidase Genes in Maize Reveal Essential Roles in Abiotic Stress Tolerance - Xi, Yan; Hu, Wenjing; Zhou, Yue; Liu, Xiang; Qian, Yexiong (Frontiers in Plant Science, 2022)
Polyamines (PAs) play a critical role in growth and developmental processes and stress responses in plants. Polyamine oxidase (PAO) is a flavin adenine dinucleotide (FAD)-dependent enzyme that plays a major role in PA catabolism. Here, for the ﬁrst time, PAO genes in maize were screened for the whole genome-wide and nine ZmPAO genes were identified in this study, named as ZmPAO1-9. Based on structural characteristics and a comparison of phylogenetic relationships of PAO gene families from seven representative species, all 9 PAO proteins in maize were categorized into three distinct subfamilies. In addition, chromosome location and schematic structure revealed an unevenly distribution on chromosomes and evolutionarily conserved structure features of ZmPAO genes in maize, respectively. Also, the analysis of cis-acting elements of promoter regions revealed that ZmPAO genes might be mainly involved in hormone regulation and adversity stress. Furthermore, transcriptome analysis demonstrated that ZmPAO genes showed differential expression patterns at diverse developmental stages of maize, suggesting that these genes may function in multiple tissues. Further, through qRT-PCR validation, these genes were confirmed to be responsive to heat, drought and salinity stress treatments in three various tissues, indicating their potential roles in abiotic stress responses. Eventually, ZmPAO6 gene was overexpressed in transgenic Arabidopsis to verify its function under heat stress. Compared with wide-type (WT) Arabidopsis, transgenic Arabidopsis plants overexpressing ZmPAO6 exhibited enhanced tolerance to heat stress through mediating polyamine catabolism, which might result in alterations in polyamine content and some various physiological indicators, indicating that ZmPAO6 may play a crucial role in enhancing heat tolerance of transgenic Arabidopsis through the involvement in several different metabolic pathways. Further, the expression analysis of related genes of antioxidant enzymes including glutathione peroxidase (GPX) and ascorbate peroxidase (APX) demonstrated that ZmPAO6 can enhance heat resistance in transgenic Arabidopsis through modulating heat-induced H2O2 accumulation in polyamine catabolism. Taken together, our results are the first to report the ZmPAO6 gene response to heat stress in plants and will serve to present an important theoretical basis for further unraveling the function and regulatory mechanism of ZmPAO genes in growth, development and adaptation to abiotic stresses in maize.